ENTRE TEXTE ET SCENE, LE JEU DE L’ACTEUR DANS LA COMÉDIE ITALIENNE DE LA RENAISSANCE. LEONE DE’ SOMMI, “QUATTRO DIALOGHI IN MATERIA DI RAPPRESENTAZIONI SCENICHE” - Théa PICQUET (Studia Universitatis Babeş-Bolyai. Philologia, 2020)
Between Text and Stage: Acting in Italian Renaissance Comedy Leone de’ Sommi, Quattro dialoghi in materia di rappresentazioni sceniche.  In his treatise, Quattro dialoghi in materia di rappresentazioni sceniche, Leone de’ Sommi gives the earliest indications of his time on comedy acting and staging. Our purpose is to analyze the relationship between text and stage in order to set into relief what pertains to acting. After a brief presentation of the author, we’ll focus on the text and its many transformations, the date when it was written as well as its structure. We’ll then proceed with the advice given to the actors, to the stage director, the importance of the setting and of lights. Finally, we’ll insist on the historical significance of the treatise and emphasize it innovative nature.